PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DI BADAN NARKOTIKA NASIONAL (BNN) KOTA KEDIRI - Okta Purnamasari (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
The purpose of this research was to find out, (1) The effect of organizational culture toward employees performance at BNN Kota Kediri, (2) The effect of organizational commitment toward employees performance at BNN Kota Kediri, (3) The effect of organizational culture and organizational commitmen toward employees performance at BNN Kota Kediri. This is a quantitative research by using multiple analysis regresi. The population in this research were 37 employees at BNN Kota Kota Kediri. The sampling technique of this research is sensus. And the instrument is questionnaire to find out the statistical variabel data research of organizational culture, organizational commitment, and employees performance. This research also using Uji linieritas and uji multikolinieritas for data analysis technique. This research found out that (1) Organizational culture were positively related toward employees performance at BNN Kota Kediri. (2) Organizational commitment were positively related toward employees performance at BNN Kota Kediri. (3) Organizational culture and organizational commitment were positively toward employees performance at BNN Kota Kediri.